Book Review: A Handbook for Men's Clothing of the Late 15th Century by Anna Malmborg and Willhelm Schütz - Jens Börner (EXARC, 2019)
Although there is a wide variety of publications about costume history and of single archaeological sites with textile remains of period clothing, the number of books that interdisciplinarily cover the fashion of past eras in the context of different source categories is, frankly, really small. Some attempts to draw a complete image of medieval fashion simply fail just because of the scale of it; others try to approach the topic from the side of art history. In the periphery of living history or reenactment, several illustrated books emerged - some of which gained vast popularity- including guides for reconstructing, or, at least, re-sewing clothing from several periods, most of them with a very narrow focus. This book takes the same approach as the latter, and aims for the most popular period among reenactors.